2022
DOI: 10.3390/ma15041437
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Tribological Properties of Spark-Plasma-Sintered Ti3SiC2-Pb-Ag Composites at Elevated Temperatures

Abstract: Ti3SiC2-PbO-Ag composites (TSC-PA) were successfully prepared using the spark plasma sintering (SPS) technique. The ingredient and morphology of the as-synthesized composites were elaborately investigated. The tribological properties of the TSC-PA pin sliding against Inconel 718 alloys disk at room temperature (RT) to 800 °C were examined in air. The wear mechanisms were argued elaborately. The results showed that the TSC-PA was mainly composed of Ti3SiC2, Pb, and Ag. The average friction coefficient of TSC-PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Currently, an intense search for self-lubricating materials and surface layers that contain solid lubricants embedded in their matrix is underway [ 11 , 12 , 13 , 14 , 15 ]. They can be produced using: powder metallurgy (resulting in the formation of self-lubricating materials), laser alloying (resulting in the formation of technological superficial layers) or thermal spraying as well as PVD and CVD techniques (resulting in the formation of coatings) [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The disadvantages of self-lubricating coatings are limited service life, difficulties in refilling, oxidation, aging-related degradation and poor adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, an intense search for self-lubricating materials and surface layers that contain solid lubricants embedded in their matrix is underway [ 11 , 12 , 13 , 14 , 15 ]. They can be produced using: powder metallurgy (resulting in the formation of self-lubricating materials), laser alloying (resulting in the formation of technological superficial layers) or thermal spraying as well as PVD and CVD techniques (resulting in the formation of coatings) [ 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The disadvantages of self-lubricating coatings are limited service life, difficulties in refilling, oxidation, aging-related degradation and poor adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [22] reported the microstructure and mechanical properties of composites obtained by spark plasma sintering of Ti 3 SiC 2 -15 vol.%Cu mixtures, and the microstructure and tribological properties of spark-plasma sintered Ti 3 SiC 2 -Pb-Ag composites at elevated temperatures were further investigated in [23]. The authors of [24] explored the effect of Al 2 TiO 5 content and sintering temperature on the microstructure and residual stress of Al 2 O 3 -Al 2 TiO 5 ceramic composites, and the effects of material design and sintering process on residual stresses were expounded from macro-and micro-levels.…”
mentioning
confidence: 99%